WAFERS: AN INNOVATIVE ADVANCEMENT OF ORO-DISPERSIBLE FILMS - Dey, Paramita; Ghosh, Arnabi (International Journal of Applied Pharmaceutics, 2016)
The formulation of oral disintegrating films has led to the development of wafers which has modified itself in the recent past years. Wafers are more advantageous over other conventional dosage forms as well as from other oral disintegrating solid dosage forms. The major difficulty in formulating wafers is the choice of drugs to be incorporated. Wafers with low dose of active pharmaceutical ingredient (API) and with a good mouth feel are prepared for making it more patients compliant. The manufacturing procedures are quite similar to oral disintegrating film but the composition of polymers may vary. The wafers requires expensive packaging and care should be taken while handling, storage & transport. In spite of these hardships, wafers have become popular between geriatric and paediatric population because of its ease of administration and bioavailability. Keywords: Transmucosal route, Oral films, Wafers, Fast dissolving dosage forms, Oral administration